Exploring the relationship between coffee consumption and kidney function: A scoping review - Syahidah Nida Amani; Razan Shabrina Malahati; Almira Sitasari; Agus Wijanarka; Tri Siswati (DAPU Aceh Publishing, 2025)
In recent years, dialysis has become a routine procedure for millions of patients with advanced CKD, with estimates suggesting that more than 3 million people worldwide are undergoing dialysis. This surge has been attributed to lifestyle factors, an aging population, and the increasing incidence of non-communicable diseases such as diabetes and hypertension, which are major risk factors for kidney dysfunction. One factor that is being investigated is coffee consumption as coffee consumption has increased dramatically in recent years. This scoping review aims to analyze research articles on the relationship between coffee consumption and kidney function. A total of 22 studies were identified during the database search. After excluding studies that did not meet the inclusion and exclusion criteria, 11 studies were obtained. After excluding studies that did not meet the inclusion and exclusion criteria, a total of 10 studies were obtained. The study suggests that coffee consumption has a complex relationship with kidney health. The effects of coffee consumption also depend on the amount, pattern and time of consumption, coffee components, genetics, and environmental factors. While the results suggest potential for positive outcomes, more research is needed to specifically and deeply explore these relationships and their long-term effects on human health.